Checklist and bilingual key to the genera of Scutelleridae (Hemiptera: Heteroptera) from Mexico, with new distribution records for the state of Oaxaca - Guzmán-Vásquez, Héctor M.; Martínez-Martínez, Laura (Zootaxa, 2025)
For the first time, we provide a checklist and a bilingual key to the genera of Scutelleridae (Hemiptera: Heteroptera) from Mexico, with new distribution records for the state of Oaxaca. The scutellerid fauna of Mexico is comprised of 35 species, two subspecies, 14 genera and two subfamilies, of which seven species are endemic. The best-represented genus in Mexico is Symphylus with eight species. The states of Veracruz and Oaxaca have the highest richness with 17 and 15 species, respectively. The new records for Oaxaca correspond to the species: Camirus moestus (Stål), Orsilochides scurrilis (Stål), Stethaulax marmorata (Say), Symphylus caribbeanus Kirkaldy (all Pachycorinae) and Augocoris gomesii Burmeister (Scutellerinae). We add new locality records for Pachycoris klugii Burmeister and Tetyra antillarum Kirkaldy in Oaxaca. We provide data on the possible coprophagy of Sphyrocoris obliquus (Germar) (Pachycorinae). Stethaulax marmorata is a new state and national record. Also, we document new associations of scutellerids with plants and, a new host record for T. antillarum.